Predicting and overcoming resistance to CDK9 inhibitors for cancer therapy - Chen Hu; Lijuan Shen; Fengming Zou; Yun Wu; Beilei Wang; Aoli Wang; Chao Wu; Li Wang; Jing Liu; Wenchao Wang; Qingsong Liu (Elsevier, 2023)
Abnormally activated CDK9 participates in the super-enhancer mediated transcription of short-lived proteins required for cancer cell survival. Targeting CDK9 has shown potent anti-tumor activity in clinical trials among different cancers. However, the study and knowledge on drug resistance to CDK9 inhibitors are very limited. In this study, we established an AML cell line with acquired resistance to a highly selective CDK9 inhibitor BAY1251152. Through genomic sequencing, we identified in the kinase domain of CDK9 a mutation L156F, which is also a coding SNP in the CDK9 gene. By knocking in L156F into cancer cells using CRISPR/Cas9, we found that single CDK9 L156F could drive the resistance to CDK9 inhibitors, not only ATP competitive inhibitor but also PROTAC degrader. Mechanistically, CDK9 L156F disrupts the binding with inhibitors due to steric hindrance, further, the mutation affects the thermal stability and catalytic activity of CDK9 protein. To overcome the drug resistance mediated by the CDK9-L156F mutation, we discovered a compound, IHMT-CDK9-36 which showed potent inhibition activity both for CDK9 WT and L156F mutant. Together, we report a novel resistance mechanism for CDK9 inhibitors and provide a novel chemical scaffold for the future development of CDK9 inhibitors.